Vegetation Classification: Need we Dissociate Environmental Terminologies from the Physiognomic Nomenclature? - Meher Homji, V. M. (Indian Forester, 1978)
The tendency of the earlier authors of combining environmental terms iu vegetational nomeoclature continues to survive. Though this is indispensable in certain cases, in moist vegetation types, physiognomy can be described by its own characteristics without reference to its habitat. Noteworthy species of the formation may be associated with the physiognomy rather than the geographical, climatic and edaphic traits attention is drawn to some cases of inappropriate uses of environmental appellations in naming the forest types of India.